The psychoanalytic session and psychoanalytic clinical facts - Kadyrov I.M. (Консультативная психология и психотерапия, 2010)
In the paper the author discusses epistemological problems one faces in the psychoanalytic research under the special condition of psychoanalytic situation. The authors also discusses the nature of the «empirical data» and «clinical facts» the analyst deals during a psychoanalytic session. Clinical facts are understood as lively psychological events which reveal the internal world of the patient in his immediate relationship with the analyst. Perception and formulation of a clinical fact by the analyst is influenced by the emotional movements and events in the session, by the personal conditions of the analyst, by his implicit working model and official theory and by the setting.